Al2O3-Coated Ni/CeO2 nanoparticles as coke-resistant catalyst for dry reforming of methane. Issue 24 (6th November 2020) - Yang, Euiseob; Nam, Eonu; Lee, Jihyeon; Lee, Hojeong; Park, Eun Duck; Lim, Hankwon; An, Kwangjin
Abstract : To mitigate catalyst deactivation during the dry reforming of methane, Ni/CeO2 catalysts composed of monodisperse Ni nanoparticles supported on CeO2 nanorods are designed and coated with Al2 O3 layers by atomic layer deposition. Abstract : Nickel is considered an economically feasible catalyst for the dry reforming of methane (DRM) owing to its high activity. Because the highly endothermic DRM requires a high reaction temperature to activate both CH4 and CO2, deactivation of the Ni catalyst may be induced by sintering and carbon coking. To mitigate catalyst deactivation, Ni/CeO2 catalysts composed of monodisperse Ni nanoparticles supported on CeO2 nanorods are designed and coated with Al2 O3 layers by atomic layer deposition (ALD). The performance of the catalyst in DRM and amount of carbon deposited are correlated with the thickness of the Al2 O3 layer in the Ni/CeO2 /Al2 O3 catalysts. As the number of ALD cycles increases from 1 to 10, the conversion of CO2 and CH4 at 700 and 800 °C decreases, but the Ni/CeO2 /Al2 O3 catalysts remain coke-free as thermogravimetric analysis shows no weight loss up to 800 °C. The Al2 O3 layer generated by ALD curtails the coking substantially, but the weakly metallic character of Ni and blocking of Ni sites by the Al2 O3 layer are the major factors contributing to decreasing the catalytic conversion. The ALD technique provides an efficient way to fabricate atomically controlled oxide layers for improving the stability of catalysts against coke deposition and sintering.